Numerical investigation of the early flight phase in ski-jumping - Gardan, N.; Schneider, A.; Polidori, G.; Trenchard, H.; Seigneur, J. M.; Beaumont, F.; Fourchet, F.; Taiar, R. (Journal of Biomechanics, 2017)
The purpose of this study is to develop a numerical methodology based on real data from wind tunnel experiments to investigate the effect of the ski jumper`s posture and speed on aerodynamic forces in a wide range of angles of attack. To improve our knowledge of the aerodynamic behavior of the ski jumper and his equipment during the early flight phase of the ski jump, we applied CFD methodology to evaluate the influence of angle of attack (a = 14°, 21.5°, 29°, 36.5° and 44°) and speed (u = 23, 26 and 29 m/s) on aerodynamic forces in the situation of stable attitude of the ski jumper`s body and skis. The standard k-k- turbulence model was used to investigate both the influence of the ski jumper`s posture and speed on aerodynamic performance during the early flight phase. Numerical results show that the ski jumper`s speed has very little impact on the lift and drag coefficients. Conversely, the lift and drag forces acting on the ski jumper`s body during the early flight phase of the jump are strongly influenced by the variations of the angle of attack. The present results suggest that the greater the ski jumper`s angle of inclination, with respect to the relative flow, the greater the pressure difference between the lower and upper parts of the skier. Further studies will focus on the dependency of the parameters with both the angle of attack a and the body-ski angle ß as control variables. It will be possible to test and optimize different ski jumping styles in different ski jumping hills and investigate different environmental conditions such as temperature, altitude or crosswinds.